Lung and cardiac ultrasonography in intensive care - DOĞANAY, Zahide; YILMAZ, Ayşe; SOYLU, Veysel Garani (MediHealth Academy, 2022)
Ultrasonography is an imaging tool that is increasingly used in the diagnosis and follow-up of many lung and heart diseases. Full lung ultrasonography is the examination of both hemithorax and protocols and image definitions have been created to make the examination more systematic and accurate. Cardiac ultrasonography is used to evaluate a moving organ. It requires users to be able to detect and interpret dynamic and variable values. Another feature of ultrasonography is its ability to guide interventional procedures. Ultrasonography will develop in the future and will be used more as a modern diagnostic tool in lung and heart evaluation by specialists.
Keywords: 3. Good health